Growth and yield of common bean cultivars at two soil phosphorus levels under biological nitrogen fixation - Araújo, Adelson Paulo; Teixeira, Marcelo Grandi; Almeida, Dejair Lopes de (Pesquisa Agropecuaria Brasileira, 2000)
The genotypic differences on growth and yield of common bean (Phaseolus vulgaris L.) in response to P supply were evaluated in a field experiment under biological N2 fixation. Eight cultivars were grown at two levels of applied P (12 and 50 kg ha-1 of P _ P1 and P2 respectively), in randomized block design in factorial arrangement. Vegetative biomass was sampled at three ontogenetic stages. The effects of genotype and phosphorus were significant for most traits, but not the genotype x phosphorus interaction. The cultivars presented different patterns of biomass production and nutrient accumulation, particularly on root system. At P1, P accumulation persisted after the beginning of pod filling, and P translocation from roots to shoots was lower. The nodule senescence observed after flowering might have reduced N2 fixation during pod filling. The responses of vegetative growth to the higher P supply did not reflect with the same magnitude on yield, which increased only 6% at P2; hence the harvest index was lower at P2. The cultivars with highest yields also presented lower grain P concentrations. A sub-optimal supply of N could have limited the expression of the yield potential of cultivars, reducing the genotypic variability of responses to P levels.